2017
DOI: 10.1007/s13402-017-0341-9
|View full text |Cite
|
Sign up to set email alerts
|

A step-by-step microRNA guide to cancer development and metastasis

Abstract: The impact and the dynamic potential of miRNAs with oncogenic or tumor suppressor properties in each stage of the multistep process of tumorigenesis, and in the adaptation of cancer cells to stress, are discussed. We propose that the balance between oncogenic versus tumor suppressive miRNAs acting within transcription factor-miRNA regulatory networks, influences both the multistage process of neoplastic transformation, whereby normal cells become cancerous, and their stress responses. The role of specific tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 385 publications
0
124
0
5
Order By: Relevance
“…MicroRNAs (miRNAs) are small non‐coding RNAs of ~22 nucleotides in length that play important roles in cell growth, development, differentiation, and apoptosis . Studies have shown that miRNAs are clearly differentially expressed in different cancer types, and that the expression of certain miRNAs can serve as both a marker for cancer development and a target for cancer treatment, suggesting that miRNAs may be licensed as oncogenes or tumor suppressors . MiR‐196b promotes LC cell migration and erosion by targeting to reduce GATA6 levels .…”
Section: Gata6 and Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small non‐coding RNAs of ~22 nucleotides in length that play important roles in cell growth, development, differentiation, and apoptosis . Studies have shown that miRNAs are clearly differentially expressed in different cancer types, and that the expression of certain miRNAs can serve as both a marker for cancer development and a target for cancer treatment, suggesting that miRNAs may be licensed as oncogenes or tumor suppressors . MiR‐196b promotes LC cell migration and erosion by targeting to reduce GATA6 levels .…”
Section: Gata6 and Human Cancersmentioning
confidence: 99%
“…28 Studies have shown that miRNAs are clearly differentially expressed in different cancer types, and that the expression of certain miRNAs can serve as both a marker for cancer development and a target for cancer treatment, suggesting that miRNAs may be licensed as oncogenes or tumor suppressors. [29][30][31][32][33] MiR-196b promotes LC cell migration and erosion by targeting to reduce GATA6 levels. 34 However, a comprehensive study of the relationship between GATA6 and LC can be found to be controversial in the role of GATA6 in LC.…”
Section: Gata6 and Lung Cancermentioning
confidence: 99%
“…There are several hallmarks that provide cancer cells with their notable characteristics [5]. It is also well known that multiple cellular signaling pathways and (extra) cellular components may govern the development of this disease [5, 6], and it has amply been shown that exogenous and endogenous carcinogens may cause mutations in the genome, driving the conversion of normal cells into cancerous cells [6, 7]. Cancer may also present itself as a genetic disease, since cancer-causing mutations in tumor suppressor genes and/or DNA repair genes may be transferred from one generation to the next [8].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant miRNAs can function as either oncogenes or tumor suppressors in various types of carcinomas. 17 Overexpression of miR-196b upregulates the expression levels of VIM and MMP-2 and downregulates the expression of CDH1, thereby promoting the metastasis of non-small cell lung cancer by inducing epithelial-mesenchymal transition (EMT) signaling. 18 In addition, miR-19a, miR-24, miR-155, and miR-181b can be used to assess the degree of cancer risk in breast cancer patients.…”
mentioning
confidence: 99%